Karakteristik dan Sebaran Mineralisasi Logam Mulia dan Logam Dasar di Wilayah Kabupaten Sanggau, Kalimantan Barat - Isnu Hajar Sulistyawan (Pusat Survei Geologi, 2017)
Sanggau and surrounding areas are geologically have various of the type and age of rocks. Therefore, this study is aimed to explore the possible influence of the diversity of geological conditions on mineralization occurring in this region, especially concerning the presence of metal minerals. As an implementation, geological surveys consist of field observations and laboratory analysis have been conducted to determine the chemical characteristics of mineralization occurring in the region. The Atomic Absorbtion Spectrometry method was chosen to determine the content of each element of base metal and precious metal contained in the rock in the region. From the analysis results it is known that there is a tendency of distribution of elementary metal elements and precious metal elements scattered in different areas. The Late Oligocene-Early Miocene Sintang Intrusive rocks are generally exposed in the northern part of the research area, in which by the chemical analysis contains more dominant elements which are associated with precious metals such as Cu and Au. While in the southern research area which is generally occupied by the Cretaceous Granodiorite Mensibau Intrusive Rocks based on chemical analysis, containing the elements associated with base metals such as Pb and Zn. This pattern shows that both types and age of different intrusive rocks bring different mineralized products.Keywords : base metal, precious metal, intrusive, mineralisation